Food Events and the Experience Economy: A Netnographic Examination of the Case of Dîner En Blanc - Liu, Zhuosi (Auckland University of Technology, 2020)
The ‘experience economy’ is a term that continues to be applied by tourism and hospitality researchers although it emerged over 20 years ago. According to Pine and Gilmore (1998), the next level after the service economy is the experience economy; it is an upscaling of the services economy which involves the consumer in the production of goods and services. The evaluation of event experience has been investigated by various researchers adopting different frameworks. In addition, affective, cognitive and behavioural components are the ordinary measurements researchers use to evaluate an experience that is determined by psychological perceptions. Conversely, Pine and Gilmore offered the four experience realms to investigate attendees’ experiences from an additional perspective: Education, Entertainment, Esthetic and Escapism. However, there is limited understanding of how the experience economy applies to the journey of an event attendee’s experience of a food event and the role of the consumer as the producer of the event as well. This study sought to understand attendees as prosumers at Dîner en Blanc and explore the level of experience at each stage of the event using the four realms of the experience economy. The study employed a qualitative methodology using netnography. Data were collected from 12 bloggers who participated in Dîner en Blanc from 2015 to 2020. The use of netnography makes an additional realm of experience more discoverable. The evaluative realm emerged as an additional realm of experience in Dîner en Blanc. The combined realm of experiences, the ‘sweet spot’, a rare experience according to Pine and Gilmore (1998), was also discovered in the context of this study. An integrated schema of the journey of Dîner en Blanc attendees and the experience economy contributes to both event management practice and theory in appreciating the different stages of experience in designing and co-creating prior to the event, during the event and after the event, for successful event marketing and management.
Keywords: Netnography; Event; Food events; Experience economy; Experience; Diner en Blanc